Walt Whitman's Democracy : Between Transcendentalism and Realism - Belkhasher, Khalid Y. (Author (مجلة الأندلس للعلوم الاجتماعية والتطبيقية, 2023)
Walt Whitman's Democracy : Between Transcendentalism and Realism